New Frontiers in Artificial Intelligence JSAI-isAI 2009 Workshops, LENLS, JURISIN, KCSD, LLLL, Tokyo, Japan, November 19-20, 2009, Revised Selected Papers - Nakakoji, Kumiyo; Murakami, Yohei; McCready, Eric.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of 4 workshops held at the JSAI International Symposia on Artificial Intelligence 2010, in Tokyo, Japan, in November 2009. The 24 revised full papers presented were carefully reviewed and selected from 61 submissions. The papers are organized in the workshop sections Logic and Engineering of Natural Language Semantics (LENLS), Juris-Informatics (JURISIN), Knowledge Collaboration in Software Development (KCSD), and Learning with Logics and Logics for Learning (LLLL).
Juris-Informatics -- Third International Workshop on Juris-Informatics -- Using BATNAs and WATNAs in Online Dispute Resolution -- Thai Succession and Family Law Ontology Building Using Ant Colony Algorithm -- Reflective Visualization of the Agreement Quality in Mediation -- Implementing Temporal Defeasible Logic for Modeling Legal Reasoning -- Evaluating Cases in Legal Disputes as Rival Theories -- Law-Aware Access Control: About Modeling Context and Transforming Legislation -- Knowledge Collaboration in Software Development -- 3rd International Workshop on Supporting Knowledge Collaboration in Software Development (KCSD2009) -- On the Central Role of Mailing Lists in Open Source Projects: An Exploratory Study -- A Proposal of TIE Model for Communication in Software Development Process -- Identifying the Concepts That Are Searchable with Keywords in Code Search Engines -- On the Use of Emerging Design as a Basis for Knowledge Collaboration -- A Time-Lag Analysis for Improving Communication among OSS Developers -- Comparison of Coordination Communication and Expertise Communication in Software Development: Motives, Characteristics, and Needs -- Logic and Engineering of Natural Language Semantics -- 6th International Workshop on Logic and Engineering of Natural Language Semantics (LENLS 6) -- Representing Covert Movements by Delimited Continuations -- Problems with Intervention and Binding into Relations -- A Translation from Logic to English with Dynamic Semantics -- Semantics of Possibility Suffix (3z(B(Rar)e(3y (B-- An Adaptive Logic for the Formal Explication of Scalar Implicatures -- Two Kinds of Procedural Semantics for Privative Modification -- On the Nature and Formal Analysis of Indexical Presuppositions -- Non-standard Uses of German 1st Person Singular Pronouns -- Learning with Logics and Logics for Learning -- The Sixth Workshop on Learning with Logics and Logics for Learning (LLLL2009) -- Inferability of Unbounded Unions of Certain Closed Set Systems -- Mining Frequent k-Partite Episodes from Event Sequences -- Learning from Positive Data Based on the MINL Strategy with Refinement Operators -- Computing Minimal Models by Positively Minimal Disjuncts.s
Keywords: Computer science; Database management; Data mining; Information storage and retrieval systems; Information systems; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl.Internet).; Information Storage and Retrieval; Database Management; Mathematical Logic and Formal Languages; Data Mining and Knowledge Discovery